2018
DOI: 10.3102/0034654318805924
|View full text |Cite
|
Sign up to set email alerts
|

Gentrification and Academic Achievement: A Review of Recent Research

Abstract: Research in the neighborhood effects tradition has primarily concerned itself with understanding the consequences of growing up in high-poverty neighborhoods. In recent years, however, the in-migration of relatively affluent households into disinvested central city neighborhoods—commonly referred to as gentrification—has markedly risen, transforming the racial, socioeconomic, and institutional composition of many urban neighborhoods. This article examines what existing literature reveals about what these chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 152 publications
1
33
0
1
Order By: Relevance
“…For example, at the center of single-industry cities and rural towns-from Motor City to farming village-is an economic dependence that benefits industries and the policymakers supporting them and, when industries restructure, hurts local communities (Campbell, 2017;Lyson & Falk, 1993;Martelle, 2014;Sherman, 2009;Theobald & Alsmeyer, 1993). Gentrification is another example: Urban renewal plans have raised rents, built luxury apartments, and attracted high-end businesses to cities, while pushing out low-income communities of color Lipman & Haines, 2007;Pearman, 2019;Wyly & Hammel, 2004). And sometimes policymakers have simply overlooked the spatialized effects of capitalism, a lapse that has, for instance, created urban and rural food deserts and limited broadband access (Stenberg et al, 2009;Walker et al, 2010).…”
Section: Educational Redlining?mentioning
confidence: 99%
“…For example, at the center of single-industry cities and rural towns-from Motor City to farming village-is an economic dependence that benefits industries and the policymakers supporting them and, when industries restructure, hurts local communities (Campbell, 2017;Lyson & Falk, 1993;Martelle, 2014;Sherman, 2009;Theobald & Alsmeyer, 1993). Gentrification is another example: Urban renewal plans have raised rents, built luxury apartments, and attracted high-end businesses to cities, while pushing out low-income communities of color Lipman & Haines, 2007;Pearman, 2019;Wyly & Hammel, 2004). And sometimes policymakers have simply overlooked the spatialized effects of capitalism, a lapse that has, for instance, created urban and rural food deserts and limited broadband access (Stenberg et al, 2009;Walker et al, 2010).…”
Section: Educational Redlining?mentioning
confidence: 99%
“…This approach may have some merit, but improving community organization presence has also been linked to reductions in neighborhood violence (Emory et al, 2008; Molnar et al, 2008; Sampson, 2012). Also, recent research has found that improvements in environmental conditions and educational resources may reduce youth exposure to violence (Pearman, 2019). Future research should examine social and economic resources as promising pathways for responding to youth trauma exposure in a comprehensive way.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when researchers report that supporting trauma-exposed youth will require an interdisciplinary group of voices to engage in deeper discussions about systems, policies, and practices (Thomas et al, 2019), we should be asking whose voices are included and whether those voices can acknowledge how systems, policies, and practices unjustly affect the lives and school experiences of many Black and Brown children in the United States (Anyon, 2014; B. W. Fisher et al, 2018; Ladson-Billings & Tate, 1995; Milner, 2012, 2015; Noguera, 2003; Pearman, 2019; Seider & Huguley, 2009). Drawing on these theoretical insights, my core argument is that race must be central to the research on youth trauma.…”
mentioning
confidence: 99%
“…Pearman (2019) studies that student achievement might be exerted negligible impacts under the urbanization and middle-class processes, especially for children living in peri-urban areas in the process of mobility. [20]. That we may not realize the effects of neighborhood change results from, we also automatically assume that the effects of urbanization children are experiencing are natural.…”
Section: Equality and Equitymentioning
confidence: 99%